2018
DOI: 10.17306/j.afs.2018.0557
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-diabetic effects of Auricularia auricular polysaccharides and their degradation by artificial gastrointestinal digestion - Bioactivity of Auricularia auricular polysaccharides and their hydrolysates [pdf]

Abstract: Background. Auricularia auricular polysaccharides (AAPs) derived from the dried fruit body of A. auricular are valuable compounds with many bioactivities. This research aimed to investigate the antioxidant and antidiabetic activities of these polysaccharides and their artificial gastrointestinal fluid hydrolysates (AAPHs). Material and methods. Artificially simulated gastrointestinal fluid was used to obtain polysaccharide-derived fragments, and a rat model of type 2 diabetes mellitus (T2DM) using a high-fat d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As shown in Figure 6D, the MDA level was reduced in AAPHs groups, which suggested that certain active groups were produced or exposed after the hydrolysis of AAPs and had the ability to inhibit the production of cytotoxic chemicals. Lu, A., Yu, M., Shen, M., Fang, Z., Xu, Y., Wang, S., Zhang, Y., Wang, W. (2018). Antioxidant and anti-diabetic effects of Auricularia auricular polysaccharides and their degradation by artificial gastrointestinal digestion -Bioactivity of Auricularia auricular polysaccharides and their hydrolysates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 6D, the MDA level was reduced in AAPHs groups, which suggested that certain active groups were produced or exposed after the hydrolysis of AAPs and had the ability to inhibit the production of cytotoxic chemicals. Lu, A., Yu, M., Shen, M., Fang, Z., Xu, Y., Wang, S., Zhang, Y., Wang, W. (2018). Antioxidant and anti-diabetic effects of Auricularia auricular polysaccharides and their degradation by artificial gastrointestinal digestion -Bioactivity of Auricularia auricular polysaccharides and their hydrolysates.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, after 30 minutes of digestion in an artificial gastric fluid, AAPs were further digested in the artificial intestinal fluid. As shown in Table 1, there was no difference in retention time in Lu, A., Yu, M., Shen, M., Fang, Z., Xu, Y., Wang, S., Zhang, Y., Wang, W. (2018). Antioxidant and anti-diabetic effects of Auricularia auricular polysaccharides and their degradation by artificial gastrointestinal digestion -Bioactivity of Auricularia auricular polysaccharides and their hydrolysates.…”
Section: Simulated Digestion Of Aaps In Vitromentioning
confidence: 91%
See 2 more Smart Citations